Barber–Say syndrome and Ablepharon–Macrostomia syndrome: An overview. Issue 8 (19th May 2016) - De Maria, Beatrice; Mazzanti, Laura; Roche, Nathalie; Hennekam, Raoul C.
Abstract : Barber–Say syndrome (BSS) and Ablepharon–Macrostomia syndrome (AMS) are congenital malformation syndromes caused by heterozygous mutations in TWIST2 . Here we provide a critical review of all patients published with these syndromes. We excluded several earlier reports due to misdiagnosis or insufficient data for reliable confirmation of the diagnosis. There remain 16 reliably diagnosed individuals with BSS and 16 with AMS. Major facial characteristics present in both entities, albeit often in differing frequencies, are excessive facial creases, hypertelorism, underdevelopment of the anterior part of the eyelids (anterior lamella), ectropion, broad nasal ridge and tip, thick and flaring alae nasi, protruding maxilla, wide mouth, thin upper vermillion, and attached ear lobes. In BSS a remarkable extension of the columella on the philtrum can be seen, and in both the medial parts of the cheeks bulge towards the corners of the mouth (cheek pads). Scalp hair is sparse in AMS only, but sparse eyebrows and eyelashes occur in both entities, and general hypertrichosis occurs in BSS. We compare these characteristics with those in Setleis syndrome which can also be caused by TWIST2 mutations. The resemblance between the three syndromes is considerable, and likely differences seem larger than they actually are due to insufficiently complete evaluation for all characteristics of the three entities in the past. It is likely that with time it can be concluded that BSS. AMS and Setleis syndrome form a continuum. © 2016 Wiley Periodicals, Inc.